Analysis of Factors That Affects the Investors in Conducting Business in Indonesia - Sari, Rini Kurnia (Bina Nusantara University, 2015)
Investment is needed in the development of the economy. With the decentralization of investment is expected to evolve as a whole in every province in Indonesia. Local governments need to improve the quality of economic (GDP / Capita), social (HDI) and the infrastructure to attract domestic and foreign investors. Fromthe test results showed that factors affecting investors conducting business in Indonesia is still influenced by GDP/capita, HDI and Infrastructure instead of natural resources.This study uses descriptive analysis and correlation analysis methods to look at the correlation factors that affect investors doing business in Indonesia.